Teori Resepsi Mazhab Konstanz dalam Studi Sastra - Mohammad Rokib (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2023)
The reception of contemporary literary works has evolved through interactive commentary on the internet. Unfortunately, literary studies, such as Arab and Indonesian literature, as seen in the Indonesian scholarly publication database, have yet to address this new phenomenon. The theories employed have also failed to highlight the significant nuances of horizon of expectations and repertoire in reader reception. Using a relevant literature tracking method, this article focuses on reception theory proposed by two Konstanz School scholars, Hans Robert Jauss and Wolfgang Iser. The findings indicate that the concept of literary reception theory is built upon the foundations of three predecessors: Russian Formalism, Prague Structuralism, and Gadamer's Hermeneutics. Among these predecessors, Jauss formulated the theory of reception with the horizon of reader expectations, while Iser enhanced reader response with the notion of repertoire. This article emphasizes the importance of considering reader response and the interaction between language and readers in comprehending the reception of texts holistically.